The Role of Tolang Teachers in Building Authority and Transmitting Islamic Educational Knowledge in Madura - Maszeri; Maimun (Penerbit Hellow Pustaka, 2025)
This study aims to theoretically describe the role of Tolang teachers in building authority and transmitting Islamic educational knowledge in Madura. Using a library research method, this study aims to provide a detailed explanation of the research objectives. The results of this study demonstrate that the role of Tolang teachers in building authority and transmitting Islamic educational knowledge in Madura involves several important stages, starting with identifying and building authority and spirituality, transmitting Islamic educational knowledge, developing Islamic character, and contributing to community development, as well as challenges and opportunities.